The young stellar population in NGC 247 - Rodriguez, Maria Jimena (2019)
Aims: We seek to investigate the characteristics of the young stellar population in the spiral galaxy NGC 247. In particular, we focused our attention in its hierarchical clustering distributions and the properties of the smallest groups. Methods: We used multiband Hubble Space Telescope (HST) data from three fields covering more than half of NGC 247 to select the young population. Then, through the path linkage criterion (PLC), we found compact young star groups and estimated their fundamental parameters, such as their stellar densities, sizes, number of members, and luminosity function (LF) slopes. We also performed a fractal analysis to determinate the clustering properties of this population. We built a stellar density map and dendrograms corresponding to the galactic young population to detect large structures and depict their main characteristics. Results: We detect 339 young star groups, for which we compute a mean radius of ̃60 pc and a maximum size distribution between 30 and 70 pc. We also obtain LF slopes with a bimodal distribution showing peaks at ̃0.1 and ̃0.2. We identify several candidates for HII regions that follow an excellent spatial correlation with the young groups found by the PLC. We observe that the young populations are hierarchically organized, wherein the smaller and denser structures are within larger and less dense structures. We notice that all these groups present a fractal subclustering, following the hierarchical distribution observed in the corresponding stellar density map. For the large young structures observed in this map, we obtain a fractal dimension of ̃1.6-1.8 using the perimeter-area relation and cumulative size distribution. These values are consistent with a scenario of hierarchical star formation. Full Table 3 is only available at the CDS via anonymous ftp to http://cdsarc.u-strasbg.fr (ftp://130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/626/A35